Upaya Pemerintah Dalam Mengatasi Tingkat Kemiskinan Di Indonesia - Nur Assyafaah; Timbul Dompak; Lubna Salsabila (Program Pasca Sarjana Universitas Garut, 2025)
This study looks at government initiatives to fight poverty in Indonesia. One important aspect of the poverty reduction strategy is the availability of accurate poverty data. This study uses a qualitative methodology. Research findings show that PKH, KIP, KIS, MSME Empowerment, and Rastra are some of the initiatives undertaken by the government. Rapid population growth, low education levels, rising unemployment rates, and income distribution. The poverty rate in Indonesia fell from 25.90 in 2023 to 25.22 in 2024. This indicates that some government initiatives have been successful. The government is still working to reduce the extreme poverty rate to zero by 2024. Uneven poverty is a factor in poverty. According to the report, there are 281,603,800 poor people in Indonesia. One of the challenges in reducing poverty is Indonesia's large population.